ART GALLERY AS A REPRESENTATION OF CULTURAL IDENTITY IN MALANG CITY THROUGH A MODERN ARCHITECTURAL APPROACH - Patrik Bagasseta Satria Pambudi; Erlina Laksmiani; Agus Sukandar (ARCHITENSA : Architectural Design Journal, 2026)
Malang is a major cultural and educational center with strong potential for art and tourism development. However, local cultural values, particularly the tradition of Topeng Malangan, remain underrepresented in modern public spaces and face challenges, including declining numbers of young practitioners and limited facilities. This study aims to design an art gallery that represents the city’s cultural identity through a modern architectural approach emphasizing functionality, contextuality, and sustainability. Using an empirical, descriptive, qualitative method, the research includes literature reviews, field observation, site and cultural analyses, and precedent studies of Selasar Sunaryo Art Space, the Louisiana Museum of Modern Art, and Ulen Sentalu Museum. The findings highlight architectural principles that integrate local cultural values with modern design. The proposed design accommodates exhibition, education, conservation, and social space while preserving the symbolic meaning of Topeng Malangan culture. Emphasizing spatial openness, flexibility, natural lighting, and a blend of local modern materials, the gallery is envisioned as an exhibition, educational, and social hub. Ultimately, it serves as a physical representation of Malang’s cultural identity and supports sustainable tourism and creative economic growth.